Effective communication skills for doctors a practical guide to clear communication within a hospital environment - Parrott, Teresa (Progressing your medical career series, 2011)
The book explores the different communication models that can be used within a healthcare setting and outlines how individuals can develop and improve their communication skills quickly and easily